Microstructural characterization of ceramic artifacts made using the raku technique (Research, Society and Development, 2021)
This study was carried out at the atelier “Adamas”, located in the city of Cunha, in the state of São Paulo, Brazil. The objective is to characterize the physical and mechanical properties of ceramics made using the raku technique in the Adamas atelier. As a methodology, the specimens were submitted to the following tests: Scanning Electron     Microscopy (SEM), X-ray Energy Dispersion Spectroscopy (EDS), mass loss and linear shrinkage. It was observed that the specimens were mainly composed of silicon and aluminum, which is typical of ceramics made with kaolinitic clays, possessing a plastic behavior for molding and after firing refractory. Therefore, ceramic artifacts made through the raku technique have typical chemical and physical characteristics of clay ceramics, proper adhesion of the glaze even when there are crackles originated purposely from the process, which causes the artistic artifact appropriate characteristics for use and appreciation.